IMPROVING STUDENTS’ PRONUNCIATION BY USING TONGUE TWISTER TECHNIQUE - Putri, Yara Amanda; Sada, Clarry; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research aimed to know how tongue twister can improve students’ pronunciation skill at the 7th grade students in Class 7B of SMPN 19 Pontianak in academic year 2017/2018. The research conducted through Classroom Action Research in three cycles. The subjects of this research were the 34 students in class 7B. The problems that students faced werethe students’ lack of confidence and the students’lack of ability to pronounce English words appropriately. The researcher used observation checklists, field notes, and a pronunciation test as tools to collect the data. The result showed that tongue twistertechnique could improve students’ pronunciation. Moreover, tongue twister sentences could improve the ability to use correct word stress, the ability in using correct intonation, and improve students’ ability to decrease the pauses and hesitation to pronounce the English word. The result indicate the students’ pronunciation improve of each cycle by using tongue twister technique. In the first cycle, the students’ mean score was 67%, 77,5%in the second cycle, and 89% in the third cycle. Therefore, the tongue twister technique improved students’ pronunciation skill. Keywords:Tongue Twister, Word Stress, Intonation, Pronunciation.